THE ROLE OF THERAPY IN MODULATING THE SKIN MICROBIOME IN CHILDREN WITH ATOPIC DERMATITIS - Małgorzata Piśkiewicz,; Weronika Duda,; Emilia Majewska,; Monika Domagała,; Joanna Wiewióra,; Izabela Domańska,; Aleksandra Sagan, (International Journal of Innovative Technologies in Social Science, 2025)
Objectives. Atopic dermatitis is a chronic dermatological condition characterized by epidermal barrier dysfunction, intensified pruritus, and the coexistence of other atopic diseases, most often beginning in early childhood. The disease has a multifactorial etiology involving genetic, immunological, and environmental factors, and is associated with reduced quality of life, particularly in children.Methods. A literature review was performed using PubMed, Google Scholar, and ResearchGate for studies in Polish and English using the keywords “atopic dermatitis,” “dysbiosis,” “microbiota,” “skin microbiota,” and “S. aureus.” Incomplete, off-topic, methodologically insufficient, unreliable, or outdated studies were excluded.Key findings. In children with atopic dermatitis, skin microbiota dysbiosis has been observed, manifested as reduced microbial diversity and a predominance of bacteria such as Staphylococcus aureus. In contrast, healthy skin exhibits a more diverse microbiome, with commensal bacteria like Staphylococcus epidermidis playing a crucial role in maintaining homeostasis. Dysbiosis in atopic dermatitis disrupts epidermal barrier function, exacerbates inflammatory symptoms, and facilitates colonization by pathogens. Skin microbiome fluctuations can vary depending on the therapy employed, including glucocorticosteroids, emollients, or biological treatments, which restore microbial balance.Conclusions. Microbiome-modulating therapies show potential in alleviating clinical symptoms and supporting beneficial bacteria, yet research on the impact of microbiota on the progression of atopic dermatitis, especially in children, remains limited. Further studies are necessary to better understand the disease mechanisms, develop more targeted therapeutic approaches, and evaluate the long-term efficacy of microbiome-focused treatments.